Tropospheric ozone over Siberia in spring 2010: remote influences and stratospheric intrusion - Antoine Berchet; Jean-Daniel Paris; Gérard Ancellet; Kathy S. Law; Andreas Stohl; Philippe Nédélec; Michael Yu. Arshinov; Boris D. Belan; Philippe Ciais (Tellus B: Chemical and Physical Meteorology, 2013)
We have identified and characterised different factors influencing the tropospheric ozone over Siberia during spring 2010. This was done by analysing in-situ measurements of ozone, carbon dioxide, carbon monoxide, and methane mixing ratios measured by continuous analysers during an intensive airborne measurement campaign of the YAK-AEROSIB project, carried out between 15 and 18 April 2010. The analysis and interpretation of the observations, spanning 3000 km and stretching from 800 to 6700 m above ground level, were enhanced using the Lagrangian model FLEXPART to simulate backward air mass transport. The analysis of trace gas variability and simulated origin of air masses showed that plumes coming from east and west of the west Siberian plain and from north-eastern China related to biomass burning and anthropogenic activity had enhanced ozone mixing ratios during transport. In one case, low ozone mixing ratios were observed over a large region in the upper troposphere above 5500 m. The air mass was transported from the marine boundary layer over the Norwegian Sea where O3 background concentrations are low in the spring. The transport was coherent over thousands of kilometres, with no significant mixing with mid–upper troposphere air masses rich in O3. Finally, the stratospheric source of ozone to the troposphere was observed directly in a well-defined stratospheric intrusion. Analysis of this event suggests an input of 2.56±0.29×107 kg of ozone associated with a regional downward flux of 9.75±2.9×1010 molecules cm−2 s−1, smaller than hemispheric climatology.